Settlement of the Hadhanah Dispute After Divorce of a Husband and Wife of Different Ethnicities in Indonesia (Case Study of Rao Pasaman) - Muhammad Abdurrazaq; Halim, Syaflin Halim (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2022)
Post-divorce child care disputes between husband and wife of different ethnicities, namely Minangkabau and Tapanuli. The purpose of this discussion is to find the factors causing the emergence of differences in child custody rights and an analysis of Islamic law on the hadhanah dispute that occurred between the two ethnic Minangkabau and Tapanuli in Rao Pasaman. The factor that causes child custody in Rao Pasaman to fall to the father is because the population is Tapanuli while Minangkabau is a minority so that more hadhanah falls to the father. This research is a type of qualitative research using an ethnographic approach, where the author conducts interviews, observations and documentation studies on aspects or targets of the research subject. It turns out that in the author's findings in resolving the hadhanah dispute after a different ethnic divorce occurred in Rao Pasaman, it was the Minangkabau ethnic who wanted to resolve the dispute through the courts, while the Tapanuli ethnic only settled up to the non-litigation stage, namely through the village head (ninik mamak and hatobangon) without being resolved through a legal route. litigation (Religious Court). From the perspective of Islamic law, the settlement of the hadhanah dispute in Rao Pasaman does not use Islamic guidance. This is because in Rao Pasaman the majority of the people are Tapanuli while the Minangkabau people have become a minority Keyword: Dispute, Hadhanah, Ethnic, Minangkabau, Tapanuli